SAT0484 Low magnesium intake is associated with increased pain in subjects with radiographic knee osteoarthritis: data from the osteoarthritis initiative. (15th June 2017) - Shmagel, A; Onizuka, N; Vo, T; Langsetmo, L; Ensrud, K; Foley, R; Valen, P
Abstract : Background: Osteoarthritis pain appears to be caused, at least in part, by alterations in peripheral and/or central nociceptive pathways.[1] As magnesium is a known mediator of nociception, we hypothesized that low magnesium intake may be associated with increased pain in radiographic knee OA. Objectives: To evaluate whether magnesium intake is associated with knee pain in radiographic knee osteoarthritis. Methods: We investigated the associations between knee pain and magnesium intake from food and supplements in 2549 participants with prevalent radiographic knee OA (Kellgren-Lawrence score ≥2) in the Osteoarthritis Initiative cohort.[2] WOMAC pain scores in the affected knee were reported annually with total follow up period of 48 months. Magnesium intake was assessed at baseline by food frequency questionnaire and dietary supplement questionnaire, and expressed in gender-specific calorie-adjusted quintiles. Analyses used generalized linear mixed effects models with repeated measures. Results: Among participants with baseline radiographic knee OA the mean total magnesium intake was 310 mg/day (SD 133) for men, and 288 mg/day (SD 118) for women, with 68% of men and 44% of women below the estimated average requirement (EAR). The mean WOMAC pain score at 0, 12, 24, 36, and 48 months of follow up was 3.5 (SD 3.8), median score 2 (IQR 0; 6). After adjustment for age, gender, BMI, caloric intake, physical activity, smoking status, alcohol use, renal insufficiency, and the use of analgesics, subjects in the lowest gender-specific quintile of magnesium intake (Q1) had, on average, 1 point higher WOMAC knee pain scores than subjects in the highest quintile (Q5): Q1 β (95% CI) 1.00 (0.61–1.39), Q2 0.69 (0.32–1.06), Q3 0.25 (-0.12–0.62), Q4 0.25 (-0.14–0.64); p<0.0001. Conclusions: In a cohort of adults with prevalent radiographic knee osteoarthritis, magnesium intake overall was below recommended. Low magnesium intake at baseline was associated with increased pain in the affected knee over 48 months of follow up. These findings may be of growing importance as the average dietary magnesium intake for humans is declining.[3] References: Thakur M, Dickenson AH, Baron R. Osteoarthritis pain: nociceptive or neuropathic? Nat Rev Rheumatol. 2014;10(6):374–380. doi: 10.1038/nrrheum.2014.47. Fawaz-Estrup F. The osteoarthritis initiative: an overview. Med Health R I. 2004;87(6):169–171. Rosanoff A, Weaver CM, Rude RK. Suboptimal magnesium status in the United States: are the health consequences underestimated? Nutr Rev. 2012;70(3):153–164. doi:10.1111/j.1753–4887.2011.00465.x. Disclosure of Interest: None declared